(untitled) (Orfeu, 2022)
The objective of this article is to apprehend and unveil the meanings attributed by the teacher Leda Maffioletti to the singing and appreciation activities developed in the discipline of music education in the Pedagogy Degree Course at the Federal University of Rio Grande do Sul (UFRGS) more specifically the musical didactic orientations of these activities regarding the articulation of her practical and theoretical knowledge for the elaboration of her classes and her students’ lesson plans. This research is situated in the field of (auto)biographical research and biographical method, which is based on authors from the (auto)biographical approach and music education who address questions about the knowledge(s) and experiences of female teachers. It is recognized that the narratives of experiences lived by Leda Maffioletti contribute to the production of knowledge and strengthening of the area of education and the fields of music education and (auto)biographical research, in the discussion about professional and human formation of pedagogues.